2020
DOI: 10.1177/0954405420947950
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on deformation behavior of magnesium alloy sheet AZ31B in pulsating hydroforming

Abstract: Magnesium alloys have been known as the next generation material for lightweight body structures. Pulsating hydroforming is an effective method to improve magnesium alloy sheet forming performance, and the formed parts are characterized by lightweight, high-specific strength and stiffness. The deformation performance of magnesium alloy sheet AZ31B with a thickness of 0.6 mm under pulsating hydroforming has been investigated by means of experimental study, numerical simulation and theoretical analysis. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It is found that the initial hydraulic pressure, the maximum hydraulic pressure, and the loading path are the basic parameters that directly affect the forming quality and dimensional accuracy. Hu et al 27 used a combination of experimental research, numerical simulation, and theoretical analysis to study the deformation properties of AZ31B magnesium alloy sheets with a thickness of 0.6 mm under pulsating hydroforming. A new evaluation index is proposed to determine the optimal forming parameters of AZ31B magnesium alloy sheet under pulsating loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the initial hydraulic pressure, the maximum hydraulic pressure, and the loading path are the basic parameters that directly affect the forming quality and dimensional accuracy. Hu et al 27 used a combination of experimental research, numerical simulation, and theoretical analysis to study the deformation properties of AZ31B magnesium alloy sheets with a thickness of 0.6 mm under pulsating hydroforming. A new evaluation index is proposed to determine the optimal forming parameters of AZ31B magnesium alloy sheet under pulsating loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important issues in metal forming processes is to improve the uniformity of the products and avoid a number of defects such as tearing and wrinkling. 12 Several factors, such as the process parameters and the die geometry, affect the formability and thickness distribution of final product obtained from the forming process. 13 On the other hand, regarding composite materials, earlier studies often focused on the maximum thickness reduction and thickness distribution of the entire bimetallic specimen.…”
Section: Introductionmentioning
confidence: 99%
“…The sheet hydroforming process has a wide range of applications in automotive, aerospace, etc, and has many advantages over conventional deep drawing. [1][2][3][4][5] In recent years, hydrodynamic deep drawing assisted by radial pressure (HDDRP) has given good results in the forming of parts with a higher limit drawing ratio. In HDDRP, the blank is formed on the surface of the punch by the pressurized liquid in the die cavity.…”
Section: Introductionmentioning
confidence: 99%